Keberfungsian Agama di Keluarga, Ancaman, Interaksi Teman Sebaya, dan Religiusitas Remaja - Siroj, Eko Yuliarti; Sunarti, Euis; Krisnatuti, Diah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Religiosity has become one of significant factors in adolescence's development, which is influenced by the closest environment among others including religion function in family, threat, and interaction factors with peers. This research aims were analyzing influence adolescence's characteristics, mother's characteristics, religion function in family, threat, and peers interaction on adolescence's religiosity. This research used cross sectional study design on 240 students of class X having intact family and living with both of their parents. The respondents come from two senior high schools and two vocational schools (public and private) in Bogor that are selected purposively because of variation of social and economic status of the families. Data was processed using descriptive analysis and inferential analysis (independent simple t-test and regression test). The result shows that parents of vocational schools’ students had higher religion function. Boys had higher threats than girls. Private school students had higher interaction than public. Boys had higher religiosity than girls. Students of vocational school and private schools had higher religiosity than ones of senior high cchool and state school. Adolescent's age, religion function in family, and adolescents’s interaction with their peers had significant influence on the religiosity of adolescents. Meanwhile, adolescent's sex, age and mother's education did not have influence on the religiosity of adolescents.